Studies on the storage stability of betacyanins from fermented red dragon fruit (Hylocereus polyrhizus) drink imparted by xanthan gum and carboxymethyl cellulose - Lim, Teck Wei; Lim, Chiau Jinq; Liow, Chun An; Ong, Seok Teng; Lim, Lay Hong; Pui, Liew Phing; Tan, Chin Ping; Ho, Chun Wai (Elsevier, 2022)
Red dragon fruit is rich in health-benefited betacyanins that are susceptible to degradation. The present study was to improve the fermented red dragon fruit drink (FRDFD) betacyanins stability by incorporating hydrocolloids solution of xanthan gum (XG, 0.15–0.30%, w/v) and carboxymethyl cellulose (CMC, 0.3–0.5%, w/v) to produce Improved-FRDFD-dH2O. Results revealed the viscosities of all samples were significantly increased as the hydrocolloids concentration increased. All the samples’ pH, aw, total soluble solids (TSS) and betacyanins content were not significantly affected by the hydrocolloids solution added. After four-week storage (25 °C), the formulation of 0.3% XG and 0.5% CMC had significantly reduced the betacyanins degradation from 60.55% to 30.66%. Meanwhile, all samples added with 0.3% XG and 0.3–0.5% CMC remained no significant change in viscosity, pH, aw and TSS after storage. These conclude the hydrocolloids solution of 0.3% XG and 0.5% CMC successfully stabilise the betacyanins in the FRDFD at 25 °C over four-week storage.